The mathematica book / Stephen Wolfram - Wolfram, Stephen
"Mathematica has defined the state of the art in technical computing for nearly a decade, and has become a standard in many of the world's leading companies and universities. From simple calculator operations to large-scale programming and interactive document preparation, Mathematica is the tool of choice at the frontiers of scientific research, in engineering analysis and modeling, in technical education from high school to graduate school, and wherever quantitative methods are used." "The Mathematica Book is the best-selling book on technical computing ever. This greatly expanded third edition presents for the first time Mathematica Version 3. As both highly readable tutorial and definitive reference, the book covers every aspect of the system. It is essential for all users, as well as for anyone interested in the revolutionary new ideas of Mathematica Version 3"